Where the Jobs Are : Entrepreneurship and the Soul of the American Economy - Dearie, John and Geduldig, Courtney (New Jersey John Wiley and Sons, 2013)
A guide to ending America's jobs emergency by accelerating the true engine of job creation--start-ups Four years after the end of the Great Recession, 23 million Americans remain unemployed, underemployed, or have left the workforce discouraged. Even worse, Washington policymakers seem out of ideas. Where the Jobs Are: Entrepreneurship and the Soul of the American Economy shows how America can restore its great
Include Graph, Notes and Index
Keywords: Entrepreneurship -- Labor policy -- Economic policy